Indian's Liking for Gold and Causes for Rising Prices of Gold (Trinity Journal of Management, IT & Media (TJMITM), 2013)
Gold has always been considered as a sacred item in the  Hindu way of life. The prices of gold have risen very fast  during the last decade. It generally happens that whenever  price of a commodity increases, its demand decreases, but  in case of gold it is not true. The prices of gold have  increased and at the same time demand has also  increased in India. In this paper titled, “Indian's Liking for The following are the limitations of the study.Gold and Causes for Rising Prices of Gold”, an attempt has Indians, Hittites, Chinese, and others. 1 been made to find out why Indians are so much attached to  gold. It has been observed that gold is much more just than  a precious metal for Indians. There are such Indian  customs that require buying of gold for special occasions  such as Diwali, Dhanteras, Akshay Tritiya etc. The liking  for gold is so deep in India that gold jewellery is transferred  from grandmother to mother, mother to daughter and so  on. The research paper will also throw light on various factors  that are responsible for increase in the price of gold. It has  been found that investment in gold has been found safe  even in the inflationary periods. Gold worldwide has been  accepted as a safe store of value. The supply of gold  cannot be increased very much at any price because it is  still difficult and costly to discover gold. Real estate market  and bank failure also affect price of gold.
Keywords: Gold; Indian culture